The psychological birth of the human infant : symbiosis and individuation - Mahler, Margaret S. (Karnac classics, 1985)
In this highly acclaimed book, Margaret S. Mahler and her collaborators break new ground in developmental psychology and present the first complete theoretical statement of Dr Mahler's observations on the normal separation-individuation process. A number of chapters are devoted to following five children epigenetically through their subphase development. A separate section describes the authors' methodology, the importance of the research setting, and the effects of changes in the setting. There are extensive appendices by Fred Pine and a useful glossary of concepts. 308 pages.